Volume-Returns Nexus in Emerging Gulf Markets: Evidence from Saudi Arabia and Dubai (2018–2024) (Journal of Academic Finance, 2025)
Purpose: The aim of this study is to examine the relationship between trading volume and stock returns in the Saudi Stock Exchange (Tadawul) and Dubai Financial Market (DFM) for 2018-2024.Method: Using a sample of 84 monthly observations for both markets from Investing.com, the research employs advanced econometric techniques, including cointegration analysis, linear regression, Granger causality testing, and Vector Autoregression (VAR) models.Results: Results exhibit a weak positive association between returns and trading volume in both markets, slightly more in Dubai. Cointegration tests identify a strong long-run equilibrium in the Saudi market, while Dubai displays several complex relationships prone to external impacts. Granger causality tests reveal no significant predictive causality in either direction, indicating that past values of returns and volume do not effectively forecast future movement. VAR analysis highlights that trading volumes are largely determined by their previous values.Originality: This study offers new insights into the dynamics of GCC markets by comparing the oil economy of Saudi Arabia with the diverse financial hub of Dubai. The findings challenge conventional volume-return models seen in developed economies, suggesting that regional structural forces dominate informational efficiency.
Keywords: Financial markets, trading volume, stock returns, cointegration, causality, VAR, Gulf markets.